Preparation and Hydrolysis of Secondary Diasulfones - B. Michel; J.F. McGarrity; H. Dahn (CHIMIA)
Two secondary α-diazosulfones, 1-tosyl-1-diazo-ethane (I) and 1-tosyl-1-diazo-isobutane (II) have been prepared and characterised. The corresponding alcohols produced by acid hydrolysis are unstable and decompose to aldehyde and p-toluene-sulfinic acid; the olefins also formed in the acid hydrolysis of I and II were found to undergo further transformations.